The open architecture of HD-PTP phosphatase provides new insights into the mechanism of regulation of ESCRT function - Deepankar Gahloth (Nature Portfolio, 2017)
Abstract HD-PTP is a tumour suppressor phosphatase that controls endocytosis, down-regulation of mitogenic receptors and cell migration. Central to its role is the specific recruitment of critical endosomal sorting complexes required for transport (ESCRTs). However, the molecular mechanisms that enable HD-PTP to regulate ESCRT function are unknown. We have characterised the molecular architecture of the entire ESCRT binding region of HD-PTP using small angle X-ray scattering and hydrodynamic analyses. We show that HD-PTP adopts an open and extended conformation, optimal for concomitant interactions with multiple ESCRTs, which contrasts with the compact conformation of the related ESCRT regulator Alix. We demonstrate that the HD-PTP open conformation is functionally competent for binding cellular protein partners. Our analyses rationalise the functional cooperation of HD-PTP with ESCRT-0, ESCRT-I and ESCRT-III and support a model for regulation of ESCRT function by displacement of ESCRT subunits, which is crucial in determining the fate of ubiquitinated cargo.